The relationship between health & economic growth development in Pakistan - Qasim , Zainab; Fatima, Rida (Advances in Social Sciences Research Journal, 2019)
This paper investigates the connections between financial development and human improvement, recognizing two chains, one from monetary development to human advancement, the other from human advancement to monetary development. “Cross country backslides show an immense relationship in the two headings, with open utilizes on prosperity and preparing, strikingly female, especially noteworthy in the chain from economic growth to human development and the endeavor rate and pay scattering immense in the human development to economic growth chain.” The essential inspiration driving this paper is to investigate the connection between human capital and monetary progress in Pakistan. “This discovering derives that, though both human headway and money related improvement should be commonly best in class, human improvement should be given progressive need.” Result demonstrates that the two central divisions which need basic degree of thought are preparing and flourishing. This objective can be cleaned by overseeing abnormal territory of GDP to these parts.